IMPLEMENTATION OF INDONESIAN COPYRIGHT FOUNDATION RIGHTS AS A ROYALTY WITHDRAWAL INSTITUTION REVIEW OF LAW NO. 28 OF 2014 CONCERNING COPYRIGHTS - Yamin, Ahmad Fachri (P3M Stia Al Gazali Barru and Meraja media, 2022)
[Full Paper] to pdf Copyright (c) 2022 The Visual journal